2017
DOI: 10.5664/jcsm.6804
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes at Two Years of Age for Premature Infants Diagnosed With Neonatal Obstructive Sleep Apnea

Abstract: Study Objectives: Neurocognitive deficits have been shown in school-aged children with sleep apnea. The effect of obstructive sleep apnea (OSA) on the neurodevelopmental outcome of preterm infants is unknown. Methods: A retrospective chart review was performed for all preterm infants (< 37 weeks) who had neonatal polysomnography (PSG) and completed neurodevelopmental assessment with the Bayley Scales of Infant and Toddler Development, 3rd Edition, between 2006 to 2015 at Riley Hospital. Exclusion criteria incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…14 In 2017, Bandyopadhyay et al reported a median AHI in their cohort of 15 premature infants was 17.4 e/h, similar to the elevated AHI found in our premature cohort as well. 15 A 2021 study by Jaleel et al evaluated the polysomnogram characteristics between children born preterm and term, confirming prematurity led to a 2.97x risk of severe OSA (21.3%) and AHI elevation (6.5 e/h) compared with non-premature children for severe OSA (12.0%) and AHI elevation (4.6 e/h). 3 There are many theories as to why preterm infants are predisposed for OSA.…”
Section: Discussionmentioning
confidence: 99%
“…14 In 2017, Bandyopadhyay et al reported a median AHI in their cohort of 15 premature infants was 17.4 e/h, similar to the elevated AHI found in our premature cohort as well. 15 A 2021 study by Jaleel et al evaluated the polysomnogram characteristics between children born preterm and term, confirming prematurity led to a 2.97x risk of severe OSA (21.3%) and AHI elevation (6.5 e/h) compared with non-premature children for severe OSA (12.0%) and AHI elevation (4.6 e/h). 3 There are many theories as to why preterm infants are predisposed for OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Protracted hospital admissions in early childhood, as are often endured by infants with RS, are a further recognized risk factor for NDD 40 . Additionally, uncontrolled sleep-disordered breathing leading to oxygen desaturation, arousals, and sleep fragmentation is a known risk factor for cognitive and behavioral problems 41 . In our cohort, NDD was significantly associated with surgical airway intervention despite adjusting for the presence of non-isolated RS, which may reflect the impact of a protracted hospital admission or early severe UAO on neurodevelopment.…”
Section: Neurodevelopmental Delaymentioning
confidence: 99%
“…Table 3 summarizes the publications on neurocognitive outcomes in infants with OSA. Three studies [54][55][56] have analyzed a relationship between AHI and neurodevelopmental scores in the infant population. These studies did not find any correlation between the two.…”
Section: Sequelaementioning
confidence: 99%